SWOT ANALYSIS ON FORMULATING OUTPATIENT SATISFACTIONS IMPROVEMENT STRATEGY IN PHARMACY DEPARTMENT OF X HOSPITAL SAMARINDA - Nurias Difa'ul Husna; Lukman Hakim; Susi Ari Kristina (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Increase in intensity has forced Pharmacy Department of X Hospital Samarinda to continously concern on patient needs and pretension as well as always tried to fulfill what patients expectation. In order to formulating the strategy to face the competition, pharmacy department of hospital needs to identify internal and external bariers. Research was aimed to know level of outpatient satisfaction in pharmacy department of X Hospital Samarinda and formulating strategy to improve outpatient satisfaction. Research design was descriptive. Instruments developed by quantitative and qualitative approach. Quantitative data obtained using questionnaires that given to outpatients in order to explore customer satisfaction. Qualitative data was obtained by indepth interview with pharmacy department chief, hospital director, employees, doctors, and supplier. Data were analised with Servqual and Strength, Weakness, Opportunity and Threat (SWOT) method. Research result showed that there were negative gap on five service dimensions. Negative gap showed that patient’s expectation were higher than services that has given by pharmacy department of hospital so patient satisfactions were not yet been achieved. Gap point dimension of services from the highest to the lowest were tangibles (-0,29), responsiveness (-0,22), reliability (-0,13), assurance (-0,11), and empathy (-0,08). Result of SWOT analysis based on analysis of internal and external sphere of pharmacy department of X Hospital Samarinda showed that pharmacy department of hospital had bigger opportunity but in same way face the weaknesses. Alternative strategies in order to improve patient satisfaction were develop structures and infrastructures, determine limitation of dispensing time, provision of drug information and counseling, and effort to increase drugs availability. Key words: pharmacy department of X Hospital Samarinda, patient satisfactions, SWOT analysis, formulating strategy